MODERNIZING THE EDUCATION PROCESS THROUGH DIGITAL TECHNOLOGIES (Modern education and development, 2025)
The rapid development of digital technologies has revolutionized the field of education, offering new methods and tools. This article examines the impact of digitalization on traditional education, e-learning platforms, artificial intelligence-based personalized learning, and virtual classrooms. Additionally, it discusses the challenges in implementing technologies in education and future opportunities.